I survived : the Japanese tsunami, 2011 - Tarshis, Lauren (Tarshis, Lauren. I survived, 2013)
In 2011, while visiting his father's hometown in Japan shortly after his death, Ben finds himself and his family being swept away by a terrible tsunami that leaves him stranded and alone in a strange country, far from home.